2013
DOI: 10.3390/s131115159
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculation of the Gas-Sensing Properties of Pt-Decorated Carbon Nanotubes

Abstract: The gas-sensing properties of Pt-decorated carbon nanotubes (CNTs), which provide a foundation for the fabrication of sensors, have been evaluated. In this study, we calculated the gas adsorption of Pt-decorated (8,0) single-wall CNTs (Pt-SWCNTs) with SO2, H2S, and CO using GGA/PW91 method based on density functional theory. The adsorption energies and the changes in geometric and electronic structures after absorption were comprehensively analyzed to estimate the responses of Pt-SWCNTs. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 23 publications
(24 reference statements)
5
48
0
Order By: Relevance
“…It is shown that functionalization with metal 1 3 nanoparticles, play a crucial role in producing gas sensors with high sensitivity [19][20][21][22][23][24][25][26][27][28]. Different experimental and theoretical studies have been performed for functionalization of carbon nanotubes and graphene, with metal nanoparticles, as the gas sensor [29][30][31][32][33][34][35]. For example, Yoosefian theoretically showed that intrinsic single wall carbon nanotube (SWCNT), cannot adsorb NH 3 gas molecules suitably, but SWCNT functionalized with palladium (Pd), facilitate adsorption of NH 3 gas, leading to the high selectivity and fast response of the device [33].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that functionalization with metal 1 3 nanoparticles, play a crucial role in producing gas sensors with high sensitivity [19][20][21][22][23][24][25][26][27][28]. Different experimental and theoretical studies have been performed for functionalization of carbon nanotubes and graphene, with metal nanoparticles, as the gas sensor [29][30][31][32][33][34][35]. For example, Yoosefian theoretically showed that intrinsic single wall carbon nanotube (SWCNT), cannot adsorb NH 3 gas molecules suitably, but SWCNT functionalized with palladium (Pd), facilitate adsorption of NH 3 gas, leading to the high selectivity and fast response of the device [33].…”
Section: Introductionmentioning
confidence: 99%
“…the gas sensitivity of the unmodified and modified MWCNTs to 50 ppm H 2 S and 50 ppm SO 2 is tested, respectively. The results show that the sensitivity of modified MWCNTs to H 2 S is enhanced 2.75 times, and the response time to H 2 S greatly reduced [16]. However, the sensitivity of modified MWCNTs to SO 2 exhibits the opposite effect.…”
Section: Nanomaterials Based Gas Sensors For Sf6 Decomposition Componmentioning
confidence: 92%
“…Geometry optimizations were performed using DMol 3 (Dassault Systèmes BIOVIA, San Diego, CA, USA) under the following conditions: 1) the spin-polarized general gradient approximation (GGA)-PBE functional [14,15] option, and 2) the DNP basis set, to predict the properties of catalyst and adsorbates (H 2 or CO). GGA-PBE based functions have been extensively used to describe systems including Pt catalysts [16][17][18] and carbon-based materials [19][20][21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%